First vaccination after birth: serious adverse events of Bacillus Calmette-Guérin (BCG) in real-world. Issue 5 (30th November 2022) - Lu, Jinmiao; Zhang, Xunjie; Xu, Hong; Li, Zhiping
ABSTRACT: The Bacillus Calmette-Guérin (BCG) vaccine is a free vaccine in China, and more than 300 million newborns have been vaccinated. Inevitably, the BCG vaccine will have some rare adverse events on the first day of life (24 hours after birth), but related reports are extremely rare. In this commentary, the authors searched the Chinese legal documents database for documents related to serious adverse events caused by BCG from January 2010 to January 2022. Fourteen pediatric cases were identified, including 7 preterm infants and 7 full-term infants. The events included 4 cases of interstitial pneumonia, 3 cases of lymphadenitis, 3 cases of septicemia, 1 case of myocarditis, 1 case of muscle atrophy, 1 case of epilepsy, and 1 case of disseminated BCG vaccine. The mortality rate of preterm infants was 100% and that of full-term infants was 28.6% (2/7). All deaths occurred within one day. The BCG vaccine has good safety for the vast majority of newborns. Clinical implication: To our knowledge, we present the largest case series of BCG vaccine-induced serious adverse events in neonates. The BCG vaccine has good safety for the vast majority of newborns. The incidence of serious adverse events with BCG vaccine may be as low as eight per million.